Molecular profile and proangiogenic activity of the adipose-derived stromal vascular fraction used as an autologous innovative medicinal product in patients with systemic sclerosis. Issue 3 (5th March 2019) - Magalon, Jérémy; Velier, Mélanie; Simoncini, Stéphanie; François, Pauline; Bertrand, Baptiste; Daumas, Aurélie; Benyamine, Audrey; Boissier, Romain; Arnaud, Laurent; Lyonnet, Luc; Fernandez, Samantha; Dignat-George, Françoise; et al.
Abstract : Objective: The autologous stromal vascular fraction (SVF) from adipose tissue is an alternative to cultured adipose-derived stem cells for use in regenerative medicine and represents a promising therapy for vasculopathy and hand disability in systemic sclerosis (SSc). However, the bioactivity of autologous SVF is not documented in this disease context. This study aimed to compare the molecular and functional profiles of the SVF-based medicinal product obtained from SSc and healthy subjects. Methods: Good manufacturing practice (GMP)-grade SVF from 24 patients with SSc and 12 healthy donors (HD) was analysed by flow cytometry to compare the distribution of the CD45− and CD45+ haematopoietic cell subsets. The ability of SVF to form a vascular network was assessed using Matrigel in vivo assay. The transcriptomic and secretory profiles of the SSc-SVF were assessed by RNA sequencing and multiplex analysis, respectively, and were compared with the HD-SVF. Results: The distribution of the leucocyte, endothelial, stromal, pericyte and transitional cell subsets was similar for SSc-SVF and HD-SVF. SSc-SVF retained its vasculogenic capacity, but the density of neovessels formed in SVF-loaded Matrigel implanted in nude mice was slightly decreased compared with HD-SVF. SSc-SVF displayed a differential molecular signature reflecting deregulation of angiogenesis, endothelial activation and fibrosis. Conclusions: Our study provides the first evidence that SSc does not compromise the vascular repair capacity of SVF, supporting its use as an innovative autologous biotherapy. The characterisation of the specific SSc-SVF molecular profile provides new perspectives for delineating markers of the potency of SVF and its targets for the treatment of SSc.